KUALITAS JASA PELAYANAN KARTU KUNING (AK1) DI DINAS TENAGA KERJA DAN TRANSMIGRASI KOTA BOGOR - Prabowo, Anugrah Dwi Cahyo; Maksudi, Beddy Iriawan; Salbiah, Euis (Jurnal Governansi, 2018)
A good governance is a government that carries out the best service in managing various types of services that exist in government institutions. The purpose of this study is finding out the relationship between the quality of yellow card service (AK1) service and community satisfaction in Manpower and Transmigration Service office of Bogor. This study used the theory of service quality from Zeithhaml, Parasuraman & Berry. The research method used descriptive method using quantitative. Data acquisition through Literature Study and Field Study. Meanwhile the data analysis technique uses Weight Mean Score (WMS) calculation. In collecting data using incidental sampling technique with the formula taro yamane with a population of service users as many as 122 people, a sample of 55 respondents. The results obtained by the assessment rate is 4.29 with a very good assessment of the results of the questionnaire processing of 55 respondents, this means that the overall service quality has been very good but there are still some shortcomings felt by users of this service as evidenced by the assessment among other dimensions because Inadequate and organized factors in the waiting room are also inadequate. Finally, the researchers suggested that there should be a focus on improving facilities and infrastructure in the yellow card service department, also expected to be able to make the latest innovations that can captivate people, good innovation is certainly the hope of many people, Researcher’s advice is for the agency to create an Information Base and Job seeker data becomes one place in the application where the job market application can be accessed by the community itself. Keywords: Service Quality, Repairs, Facilities and Infrastructure